"It feels like a mini researcher": Affirming identities of emergent multilinguals in undergraduate academic literacy classes - Kim, Won (Language and Literacy / Langue et littératie, 2026)
Informed by the ethnographically grounded insights drawing on discourse analytic perspectives, the study captures the voices of empowered student identities, illustrating how functional pedagogy may construct, challenge, and affirm identities of “vulnerable English language learners” (Ou & Gu, 2018) as identities of confident and competent text readers, writers and “mini researchers.” This teacher research project was situated in multiple sections of an academic literacy course for first-year international students at a Canadian university. The students were engaged in conducting and reporting an empirically grounded discourse analytic research project informed by systemic functional linguistics over the term. Data was generated from interviews, student-written works and journals, and teacher-researcher field notes. Through this investigation, the study demonstrates how writing classes in higher education can serve as spaces that nurture the agentive voices in L2 students who strive to expand their sense-making choices and make those choices purposely, critically, and creatively.